2018
DOI: 10.1186/s13063-018-2641-4
|View full text |Cite
|
Sign up to set email alerts
|

Progressive mobility program and technology to increase the level of physical activity and its benefits in respiratory, muscular system, and functionality of ICU patients: study protocol for a randomized controlled trial

Abstract: BackgroundEnhanced mobility in the Intensive Care Unit (ICU) could minimize the negative effects of critical illness, such as declines in cognitive, muscular, respiratory, and functional capacity. We aim to compare the functional status at ICU discharge of patients who underwent a progressive mobilization protocol versus patients who received conventional physiotherapy. We also examine the level of physical activity in the ICU, the degree of pulmonary and muscle function, and the length of stay to analyze corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
8
0
5
Order By: Relevance
“…This improvement can be explained by the clinical course of the COVID-19 and increased mobility of these patients. Corroborating our results, Schujmann et al (2018) , showed that mobility and exercise improve respiratory function in critically ill patients, besides the favorable clinical course. It is important to note that the ICU where the data were collected in the current study presents a structured early mobilization guideline ( Murakami et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…This improvement can be explained by the clinical course of the COVID-19 and increased mobility of these patients. Corroborating our results, Schujmann et al (2018) , showed that mobility and exercise improve respiratory function in critically ill patients, besides the favorable clinical course. It is important to note that the ICU where the data were collected in the current study presents a structured early mobilization guideline ( Murakami et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…Higher scores indicate worse PTSD symptoms. the physical function domain are also supported by feasibility of TUG, 110,111 handgrip strength, [111][112][113] 6-MWT, 110 and SPPB 114 in patients of acute ICU settings, as well as currently running clinical trials in critical care patients with TUG, 115 handgrip strength 115,116 and 2-MWT 105 as outcomes.…”
Section: Feasibility and Measurement Properties Of The Proposed Omismentioning
confidence: 95%
“…Lower scores indicate higher impairment EQ-5D-5L 47,48 a PICS domain: Health-related quality of life (HRQoL) Outcomes/subdomains: Mobility, self-care, usual activities, pain/discomfort, anxiety/depression, general subjective health Instrument: Brief self-report questionnaire of generic HRQoL; six items; time frame: today. EQ-5D-5L descriptive system has 5 items (1 item per subdomain), with 5-point scales from 1 to 5; generic subjective health rating with 1 additional single item, in form of a thermometer scale from 0 to 100; single index value for general health state can be calculated Cut-off score not available EQ-5D descriptive system: Higher scores indicate higher impairment EQ-5D subjective health rating: Lower scores indicate higher impairment the physical function domain are also supported by feasibility of TUG, 110,111 handgrip strength, [111][112][113] 6-MWT, 110 and SPPB 114 in patients of acute ICU settings, as well as currently running clinical trials in critical care patients with TUG, 115 handgrip strength 115,116 and 2-MWT 105 as outcomes.…”
Section: Feasibility and Measurement Properties Of The Proposed Omismentioning
confidence: 99%
“…EPM has demonstrated many benefits across the literature including reduction in healthcare costs, improved functional status at discharge and overall minimizing negative effects of critical illness. [24] One of the most well studied benefits is that of improved functional mobility at discharge. [8,25] Patients who are initiated with EPM in the first 72 hours of critical illness experience improved physical function on discharge.…”
Section: Benefits Of Epmmentioning
confidence: 99%